Isolation and Antibacterial Activity of Phenol Compounds of Ethyl Acetic Extract of Red Zinger (Zingiber officinale Roscoe var. sunti) - Lilis Siti Aisyah; Jasmansyah Jasmansyah; Sari Purbaya; Temi Resnawati (Department of Chemistry, Faculty of Sciences and Informatics, Jenderal Achmad Yani University, 2019)
In the treatment of infectious diseases, one of the serious problems faced is the occurrence of bacterial resistance to the antibiotics used. The search for new antimicrobial compounds is one of the important research activities, because of the background of the development of resistant bacterial populations. In line with this, the development of new drugs is needed to replace drugs that become resistant. This study aimed to isolate phenol compounds from the ethyl acetate extract of red ginger rhizome (Z. officinale Roscoe var. Sunti), and analyze the results of isolation using UV and FTIR spectrophotometers and test the antibacterial activity of phenol compounds to Escherichia coli and Staphylococcus aureus. The isolation stage was started by macerating the powder with n-hexane solvent then continued maceration using ethyl acetate solvents. After that the ethyl acetate extract was carried out by separation and purification of the compound using the vacuum liquid chromatography (VLC), guided gravity chromatography with thin layer chromatography (TLC) and also preparative thin layer chromatography (PTLC). From the isolation results obtained pure isolates, purity test, measurement using UV and IR spectrophotometers, and antibacterial activity tests. From the results of UV and FTIR analysis, it was concluded that the compounds obtained were groups of phenol compounds, in the form of yellow solids and showed the existence of a double bond system conjugated in the presence of –OH, C = O, C = C and –CH aromatic groups. Antibacterial activity test showed that the minimum inhibitory concentration (MIC) of Escherichia coli bacteria was 12.5% with a minimum kill concentration (MBC) of 50%, whereas for Staphylococcus aureus bacteria showed that the minimum inhibitory concentration (MIC) was 6.3% and minimum kill concentration (MBC) of 25%.